Implementasi Model Pembelajaran Kooperatif dalam Mengembangkan Sosial Emosional Anak Usia Dini di Taman Kanak-Kanak Islam Terpadu Mutiara Hati Kecamatan Kota Baru Kota Jambi - Puspita, Yessi Puspita; Zawaqi Afdal Jamil; Jamilah (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to analyse the causes of the suboptimal STAD cooperative learning model in developing children's social-emotional, find out the factors that hinder the STAD cooperative learning model in developing children's social-emotional, as well as solutions for the implementation of STAD cooperative learning model in developing children's social-emotional. The research method used descriptive qualitative research method. Data collection was conducted using observation, interview and documentation methods. Data analysis used the theory of Miles and Huberman, namely data reduction, data presentation, data verification, and data confidence testing using data triangulation. This research is located at Mutiara Hati Integrated Islamic Kindergarten, Kota Baru District, Jambi City. The results showed that the implementation of the cooperative learning model in developing children's social-emotional skills at Mutiara Hati Integrated Islamic Kindergarten, Kota Baru District, Jambi City still needs to be optimised again because many children have improved their social development through the STAD type cooperative learning model with the implementation, application, and evaluation of teachers and principals. The conclusion from the findings of this study is that the STAD model is proven effective in improving children's social-emotional development. Qualitative analysis showed that students felt more confident and were able to communicate well within the group. In addition, skills such as empathy and conflict management were also seen to increase, not only improving children's academic results, but also preparing them to become better individuals socially and emotionally